ACI Update ACI News (Journal of Airport Management, 2019)
Purpose of review The recent approval of the Bruton's tyrosine kinase inhibitor (BTKi) remibrutinib for the treatment of chronic spontaneous urticaria opened a new therapeutic class of drugs for the allergy space. This review summarizes findings from recent BTKi clinical trials, with a focus on practical considerations for the practicing allergist. Recent findings In its phase 2 trial, 4 weeks of remibrutinib treatment demonstrated remarkable efficacy in preventing food-induced anaphylaxis to peanut in adults. Additionally, in a phase 3 trial for inducible urticarias, it improved symptoms and physical stimulation threshold in patients with dermographism, cold urticaria, and cholinergic urticaria within 2 weeks. Safety signals were comparable in remibrutinib and placebo groups, with the exception of transient petechiae, which was observed in patients treated with remibrutinib in the trials for chronic spontaneous urticaria and chronic inducible urticarias, but not in the peanut allergy trial. Summary With their pan-allergen efficacy and favorable safety profiles, BTKis including remibrutinib could be effective therapeutic options for preventing food-induced anaphylaxis. Because they have rapid onset of action and transient efficacy, they may also be useful adjunct therapies for a variety of context such as food immunotherapy build-up or drug desensitizations.